Pharmacology : an introductory text - Asperheim, Mary Kaye. (Philadelphia, Pennsylvania : W. B. Saunders Company, 1981)
As in previous editions, this text is intended to provide an introduction to pharmacology. In response to many requests, the scope of this edition has been broadened to make it appropriate for students in various settings.
Unit I. Mathematics of dosage -- Unit 2. Basic pharmacology
Includes bibliographical references and index.
Keywords: PHARMACY